Mapping music documentary in post-dictatorship Chile - Farías, Martin (Universidad de Chile. Instituto de la Comunicación e Imagen, 2019)
Based on a database of 194 films made between 1994 and 2019, this article offers an exploratory study of contemporary Chilean music documentary film, providing analytical categories and research questions. These categories help to understand the strategies that filmmakers use to read musical matters from a documentary perspective. I argue that music documentary is inscribed within the so-called “turn towards the intimate” of Chilean documentary more broadly as well as within the production on memory in the post-dictatorship both in the fields of documentary film and music historiography.